Parenting Stress and Emotional/Behavioral Problems in Adolescents with Primary Headache - Operto, Francesca Felicia; Craig, Francesco; Peschechera, Antonia; Mazza, Roberta; Lecce, Paola Alessandra; Margari, Lucia (Frontiers in Neurology, 2018)
Primary headache is a frequent and disabling disorder, common among children and adolescents, and it is a painful syndrome often accompanied by functional impairment and associated with emotional and behaviour problems. The aim of this study was to investigate parenting stress and emotional/behavioural problems in adolescents affected by primary headache compared with healthy adolescents. The study population consisted of 35 adolescents and a control group of 23 healthy subjects. The assessment included the administration of clinical standardized scales such as Parent Stress Index-Short Form (PSI-SF), Pediatric Migraine Disability Assessment Score Questionnaire (PedMidas) and Child Behavior Checklist (CBCL). Headache group and control group did not differ in terms of parenting stress (p=.29). On the contrary, headache group showed more internalizing problems (p=.023), Affective Problems (p=.01), Anxious (p=.001), and Somatic Complaints (p<.001) compared with control group. In addition, we found a significant correlation between PSI domains and specific CBCL subscales in the headache group. The findings emphasize the need for expanded intervention in the clinical treatment of paediatric headache, a treatment that may also include the family members. Further research is needed.